A note on annihilators in distributive nearlattices - Calomino, Ismael Maria (2015)
In this note we propose a definition of relative annihilator in distributive nearlattices with greatest element different to that given in [5] and we present some new characterizations of the distributivity. Later, we study the class of normal and p-linear nearlattices, the lattice of filters and semi-homomorphisms that preserve annihilators.